Achieving Balanced Performance of Service Supply Chain through Structural Capital: Evidence from the Life Insurance Agency in Malaysia - Mohd Rizal Razalli; Tun Norasida Aziz; Abdul Aziz Othman (International Journal of Supply Chain Management, 2020)
Supply chain performance of a company is determined by its strategic resources. These resources may exist in the form of physical, human and structural resources. Despite many studies on these resources carried out in the past, structural resource, an element of intellectual capital, is yet to be further explored, particularly in the supply chain of the service sector. Hence, the main aim of this paper is to determine the impact of the structural capital on the Life Insurance Agency performance in Malaysia. A total of 100 respondents of agency managers of life insurance companies in Malaysia was surveyed. A quantitative approach was used and data collection through questionnaire was analyzed using the Smart-PLS 3 software version 3.0. The results indicated the significant element of the intellectual capital focusing only the on structural capital towards agency performance. Overall results revealed that structural capital have a significant influence on agency performance of Life Insurance Agency in Malaysia.